The potential role of garlic (Allium sativum) against the multi-drug resistant tuberculosis pandemic: a review - Catia Dini; Alessia Fabbri; Andrea Geraci (Istituto Superiore di Sanità, 2011)
Worldly data show the increasing incidence of Mycobacterium tuberculosis (MTB) and particularly of multi-drug resistant tuberculosis (MDR-TB). In developing countries, TB control programmes are overwhelmed by the complexity of treating MDR-TB infected people, as current tools and therapies are inadequate. MDR-TB could become the main form of TB. Risk factors that make South Africa into one of the main epicentres are analysed. A review of the studies carried out about antitubercular properties of Allium sativum both in vitro and in vivo is provided. The researches about the garlic extracts effectiveness against clinical isolates of MDR-TB are of scientific importance. Allium sativum offers a hope for developing alternative drugs. The involvement of traditional healers (TH) in the TB health management could facilitate the administration of garlic extracts to the infected patients.